Innovations in science teacher education in the Asia Pacific (Bingley, U.K. : Emerald, 2014)
The chapters in this book will focus on pre-service and in-service science teacher education, because both are equally important. With case studies for China, Japan, Korea and Taiwan topics include: Professional Development of Chemistry Teachers in the New Curriculum, Using Classroom Observation to Assist Teacher Professional Development and Science Teacher Education and Science as Inquiry: Promises and Dilemmas.
Professional development of chemistry teachers in the new curriculum / Lei Wang, Weizhen Wang, Jinghua Liu -- School-based research and learning activities : an innovative model for promoting teacher professional development / Ji Wang, Lingyuan Gu -- Professional development of chemistry teachers in China / Qing Zhou, Huiji Yue -- Occupational culture as a means of professional development for preservice science teachers in Japan / Masakata Ogawa -- Innovation in science teacher education in South Korea / Young-Shin Park -- In-service education of primary and secondary science teachers in Japan : a case study of Tokyo Gakugei university -- Status quo and opportunities in primary school science : implications for teacher education / Winnie W.M. So -- Science teacher education and science as inquiry : promises and dilemmas / Aik Ling Tan, Shirley S.L. Lim -- Innovative proposals for science teacher education in Taiwan / Hsin-Yi Liu, Yen-Ting Chen.
Print version record
Keywords: Education -- Evaluation; Education -- Teaching Methods & Materials / Science & Technology; Education -- Multicultural Education; Teacher assessment; Examinations & assessment; Science -- Study and teaching -- Asia; Science -- Study and teaching -- Pacific Area; Science teachers -- Training of -- Asia; Science teachers -- Training of -- Pacific Area